Rare bird documentation form for Northern Goshawk at Big Creek State Park, 1982 - Zaletel, Hanket al (1982)
Rare bird documentation form for a Northern Goshawk at Big Creek State Park in Polk County, IA on February 15, 1982. Epson - sheet feed